Ensuring physicomechanical performance and sustainability in alkali-activated mortars in cold weather regions with ohmic curing method - Aygun, Beyza; Uysal, Mucteba; Cosgun, Turgay; Bilir, Turhan (ELSEVIER SCIENCE SA, 2026)
This study explores the performance optimisation of alkali-activated mortars (AAMs) cured between -20 degrees C and 30 degrees C with a newly developed ohmic (electrically) curing technique. FA and GBFS were used to prepare the mortars, activated with a 12 M solution of sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) (2:1 ratio; activator-to-binder ratio = 0.58). Electrical conductivity was achieved through the addition of 2 wt% carbon black (CB) as a conducting filler with 0.5 vol% carbon fibers (CF), steel fibers (SF), and waste wire erosion (WWE) fibers as reinforcements. At 0 degrees C, CF achieved the highest compressive strength (>60 MPa) and the lowest porosity (similar to 4.8 %), demonstrating the most effective densification of the matrix. SF developed the greatest flexural strength of 13.76 MPa at -20 degrees C but dropped by 28.6 % at 30 degrees C, showing temperature sensitivity in flexural behavior. WWE produced the most stable dimensional stability with the lowest water absorption and the least variation over all the test temperatures. CB not only boosted the conductivity and the mobility of ions but also raised the temperature sensitivity and hence caused higher porosity and a decrease in freeze-thawing resistance. Analysis of variance (ANOVA) validated the most critical role of the curing temperature (p < 0.01), followed by the fiber type. Fuzzy Matrix Analysis (FMA) indicated the CF-reinforced AAMs cured at 0 degrees C as the optimum condition with the highest member grade of 0.91. Life Cycle Assessment (LCA) proved that electrical curing at 30 degrees C lowered the CO2 emissions by 26.7 % and the usage of thermal energy demand by 33 %, hence proving its potential for the sustainable application of AAMs during the building of structures in the cold region.
Keywords: Alkali-activated mortars; Electrical curing; Cold region; Physicomechanical properties; Sustainability; CONCRETE; Materials Science